Expression of CYP2W1 in colon tumors: regulation by gene methylation. (October 2007) - Gomez, Alvin; Karlgren, Maria; Edler, David; Bernal, Maria Luisa; Mkrtchian, Souren; Ingelman-Sundberg, Magnus
Introduction: CYP2W1 is a novel enzyme shown to be selectively expressed in rat fetal colon and in human colon cancer and has previously been suggested as a potential drug target for cancer therapy. Here, the expression and gene methylation of CYP2W1 were analyzed in human colon carcinoma cell lines, colon tumors and in corresponding normal colon tissue.Methods: CYP2W1 mRNA and protein expression in HepG2 and Caco-2TC7 cells and normal colon and colon tumor tissue samples were analyzed using real-time PCR and Western blotting. CYP2W1 gene methylation status in the same samples was analyzed using the sodium bisulfite sequencing method.Results & Discussion: CYP2W1 mRNA was detected in all (n = 39) tumor samples analyzed. Moreover, in 60% (12/20) of the colon tumors, CYP2W1 mRNA levels were substantially higher than in corresponding normal tissues. CYP2W1 protein was detected in most of the colon tumor samples analyzed (n = 16), which appeared to be of two apparent phenotypes: those with five- to ten-fold induced CYP2W1 (approximately 50% of the tumors), and those with low expression, harboring similar or only slightly higher amounts of CYP2W1 as compared with surrounding control tissue. Methylation analysis of the CpG island in the exon 1––intron 1 junction of the CYP2W1 gene from both cell lines, tumors and normal tissues revealed that demethylated CpG dinucleotides appeared as a requirement for high CYP2W1 gene expression.Conclusion: The expression of CYP2W1 is colon tumor-specific and is associated with methylation status of the CYP2W1 gene, suggesting a potential causal link between the gene hypomethylation and its enhanced expression.